Książkary, BookTok i Bookstagram. Tematy literackie w sieci .......... 97 - Mojska, Katarzyna (Skąd się biorą czytelnicy?, 2025)
KSIĄŻKARY (BOOKGIRLS), BOOKTOK AND BOOKSTAGRAM: LITERARY THEMES IN THE WEBThe article discusses a group of young readers active in social media as well as the trends and literary themes popular in TikTok and their impact on the book market. The author presents the advantages and drawbacks of social media.